Conocimiento de los riesgos del tabaquismo en fumadores, exfumadores y no fumadores - Ruiz Mori, Enrique (2016)
Objetive: Determine in a population of non-smokers, smokers and former-smokers, the level of knowledge of the health risks that smoking generate. Material and Methods: An epidemiological, observational, descriptive and cross-sectional research, was conducted in September 2015 in the city of Lima and Callao. Asurvey of over 18 was applied. Participants were divided into three groups, smokers, former-smokers and non-smokers. Results: The study included 2270 subjects, 744 were smokers, 752 former-smokers and 774 non-smokers. The group that mostly associated the tobacco to many diseases was the group of former-smokers, 53.8% of them mentioned to lung cancer as the most common disease related to tobacco. The non-smokers was the group that knows less often the risks of smoking. In all three groups, the most tobacco-related disease was the lung cancer, followed by myocardial infarction, while fertility was little associated. Television was the main means of dissemination about the dangers of smoking, while social networks do not have a leading role. For the former-smokers will hit more information about the risks of smoking (p<0.05). Conclusion: Former-smokers had more information on the risk of smoking. In the three groups the most tobacco-related disease was the lung cancer, and there was very little information about fertility and cigarette consumption. Formersmokers do the impacted more risk information cigarette. Television remains the main instrument to fight against smoking.